CHARACTERISTICS OF COMPOSTED BIO-TOILET RESIDUE AND ITS POTENTIAL USE AS A SOIL CONDITIONER - Triastuti, Jovita; Sintawardani, Neni; Irie, Mitsuteru (Indonesian Agency for Agricultural Research and Development - MOA, 2009)
Bio-toilet is a dry toilet where human excreta is trapped in a lignocelluloses soil matrix such as wood sawdust, then it is decomposed by aerobicÂ bacteria to organic compost rich in minerals such as N, P, and K. The study aimed to characterize the bio-toilet residue and its potential use as a soil conditioner for Jatropha curcas. The study was conducted in a private school of Daarut Tauhid in Bandung West Java. A bio-toilet S-50 type of Japan was constructed consisting of a composting chamber, mixer, heater, exhaust fan, and closet. The composting chamber was filled with 63 kg of Albizzia sawdust. Feces and urine was loaded daily by 54 students for 122-day observation. At the end of observation, the decomposed bio-toilet residue was evaluated for its physical properties such as bulk density (rb), porosity (%), and water retention (WR). Chemical properties such as pH, C/N ratio, N, P, and K, as well as microbiological properties such as numbers of bacteria, fungi, and worm eggs were evaluated at 14 and 122 days of decomposition process. Effect of the composted bio-toilet residue as plant growth media was evaluated using J. curcass as a plant indicator. Before it was used as a growth media, the composted bio-toilet residue was dried in a room temperature for 30 days. The experiment was designed in a completely randomized design 2 x 4 factorial with threereplications. The first factor was the rate of composted biotoilet residue, i.e., 0, 20, 40, and 60% based on weight of the growth media mixture (1500 g pot-1), and the second was NPK fertilizer addition at 0 and 2 g pot-1. Each pot was planted with 2-month old of J. curcas seedlings. Parameters evaluated were leaf number, leaf area, stem height, and stem diameter measured at 12 weeks after planting. The results showed that the biotoilet residue was suitable as soil conditioner because it had highporosity (76%), low bulk density (0.19 g cm-3), high water retention (2.6 ml g-1 DM), neutral pH (6.9), C/N ratio 27, and contained N, P, K, and Na of 1.73, 1.15, 1.03, and 0.88%, respectively. Its microbial count showed only two kinds of bacteria, i.e., Klebsiella pneumonia and Escherichia coli,detected at 14 and 122 days of bio-toilet usage. The composted bio-toilet residue improved vegetative performances of J. curcas as indicated by increasing leaf number, leaf area, stem height, and stem diameter.